Humanitarian logistics : performance measurement and the role of shipping (Part I) - Tan, Jovia Zining. (2013)
A relief organisation’s performance is highly dependent on how well their logistics functions, as a significant portion of a disaster relief operation is about logistics. Together with the increasing focus on transparency and accountability to donors and various stakeholders, performance measurement plays growing importance to the sector. However, although performance measurement is well established in commercial logistics, there is a lack of performance metrics in the humanitarian sector, possibly due to the unique characteristics of humanitarian logistics that inhibits defining and measuring performance.